The Third Version of the Copenhagen Psychosocial Questionnaire - Hermann Burr; Hanne Berthelsen; Salvador Moncada; Matthias Nübling; Emilie Dupret; Yucel Demiral; John Oudyk; Tage S. Kristensen; Clara Llorens; Albert Navarro; Hans-Joachim Lincke; Christine Bocéréan; et al. (Elsevier, 2019)
Introduction: A new third version of the Copenhagen Psychosocial Questionnaire (COPSOQ III) has been developed in response to trends in working life, theoretical concepts, and international experience. A key component of the COPSOQ III is a defined set of mandatory core items to be included in national short, middle, and long versions of the questionnaire. The aim of the present article is to present and test the reliability of the new international middle version of the COPSOQ III. Methods: The questionnaire was tested among 23,361 employees during 2016-2017 in Canada, Spain, France, Germany, Sweden, and Turkey. A total of 26 dimensions (measured through scales or single items) of the middle version and two from the long version were tested. Psychometric properties of the dimensions were assessed regarding reliability (Cronbach α), ceiling and floor effects (fractions with extreme answers), and distinctiveness (correlations with other dimensions). Results: Most international middle dimensions had satisfactory reliability in most countries, though some ceiling and floor effects were present. Dimensions with missing values were rare. Most dimensions had low to medium intercorrelations. Conclusions: The COPSOQ III offers reliable and distinct measures of a wide range of psychosocial dimensions of modern working life in different countries; although a few measures could be improved. Future testing should focus on validation of the COPSOQ items and dimensions using both qualitative and quantitative approaches. Such investigations would enhance the basis for recommendations using the COPSOQ III. Keywords: Psychosocial risk factors, Psychosocial working conditions, Risk assessment